Multi Criteria Analysis for Selecting Sharia Capital Market Management Investment Using ANP - Prasetyo, Hamzah Abdul Karim; Tanjung, Hendri; Devi, Abrista (Jurnal Manajemen, 2021)
The society orientation has shifted from a saving-oriented society to an investing-oriented society. Currently, investors have many choices of investment instruments to invest in the Islamic capital market. Previous studies have shown the factors that influence the capital market and influence investors' decisions to invest in the capital market. This study uses the Analytic Network Process (ANP) method to (1) determine the criteria that need to be taken into consideration in choosing an Islamic capital market investment instrument. (2) knowing the ideal investment instrument based on established criteria. The criteria used in this study include seven criteria, namely: investment performance criteria, risk criteria, liquidity criteria, macroeconomic factor criteria, individual circumstance criteria, psychological factor criteria, and demographic criteria. The respondents in this study were five experts from academics, practitioners, and regulator. The major findings of the research are (1) the criteria to be considered in choosing Islamic capital market investment instruments are divided into investor criteria and capital market criteria. Investor criteria include; psychological factors (motivation and self control), individual circumtances (financial literacy), demographics (income and education). Capital market criteria include: investment performance (capital gain, yield, and fundamental analysis), risk (financial risk, market risk and management risk), macroeconomic factors (exchange rates and gross domestic product), liquidity (liquidity ratio). (2) the alternative with the highest priority is sharia mutual funds, then sukuk and sharia stocks.